2018
DOI: 10.31803/tg-20180126094515
|View full text |Cite
|
Sign up to set email alerts
|

Thin layer drying of zucchini in solar dryer located in Osmaniye region

Abstract: In this study, the dehydration behavior of zucchini using solar assisted drying system was examined according to 22 thin layer drying models available in literature. The correlation coefficient (R2), chi-square (χ2) and root mean square error (RMSE) values were calculated to check the suitability of models by non-linear regression analysis. It was found that Cubic and Modified Midilli-1 models were the most suitable equations and their R2 values were calculated as 0.99963. χ2 and RMSE values of related mathema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
6
0
2
Order By: Relevance
“…However, this technique is affected from weather conditions and has the problems of contamination with dust, soil, sand particles, insects, the length of drying time, loss of time and product loss [6]. Solar energy assisted dryers are designed to eliminate these effects and reduce drying time [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this technique is affected from weather conditions and has the problems of contamination with dust, soil, sand particles, insects, the length of drying time, loss of time and product loss [6]. Solar energy assisted dryers are designed to eliminate these effects and reduce drying time [7].…”
Section: Introductionmentioning
confidence: 99%
“…Matlab software was used for analysis and modelling. Figure 1 shows the schematic view of the solar assisted drying system used in the study [2,3,7,24]. As can be seen from the figure, system consists of two main sections: a solar air collector and a drying chamber.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…He also found that a controlled air-flow system was suitable for drying products of higher density and drying was also more economical in a condenser dryer. Cerci et al [7] designed a drying chamber for drying zucchini, which distributed hot air uniformly. Aktas et al [8] reported that a high velocity of drying air (3 m/s) had the lowest drying time for mint leaves.…”
Section: Introductionmentioning
confidence: 99%
“…İnce tabaka kurutma denklemlerinin karmaşık dağıtılmış modellerden farklı olarak daha az veri gerektirdiği için kullanımlarının kolay olduğu ve bu sebeple geniş uygulamalara sahip olduğu literatürde görülmektedir [19,20]. Literatürde ince tabaka kuruma davranışlarının incelendiği farklı birçok çalışma bulunmaktadır [21][22][23][24][25][26][27][28][29][30][31][32]. John ve arkadaşları [21], yaptıkları deneysel çalışmada ince tabaka kurutma modeli ile kabuklu ve iç fıstığın kuruma davranışını mikrodalga yöntemi ile incelemişlerdir.…”
Section: Introductionunclassified